Impact of Renal Function on S-1 + Radiotherapy for Locally Advanced Pancreatic Cancer: An Integrated Analysis of Data From 2 Clinical Trials. Issue 7 (August 2021) - Kobayashi, Satoshi; Ueno, Makoto; Ogawa, Gakuto; Fukutomi, Akira; Ikeda, Masafumi; Okusaka, Takuji; Sato, Tosiya; Ito, Yoshinori; Kadota, Tomohiro; Ioka, Tatsuya; Sugimori, Kazuya; Sata, Naohiro; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: S-1 monotherapy with concurrent radiotherapy (RT) is a standard of care for patients with locally advanced pancreatic cancer (LAPC). Although renal dysfunction increases S-1 monotherapy toxicity, its effect in S-1 with concurrent RT remains unknown. We evaluated the effect of renal function on the safety of S-1 with RT for LAPC. Methods: We performed an integrated exploratory post hoc analysis of data from 2 prospective studies (JCOG1106 and LAPC-S1RT), where patients with LAPC received RT (50.4 Gy/28 fraction for 5.5 weeks) and concurrent S-1 (40 mg/m 2 per dose, twice daily on the day of irradiation). We split the patients into high creatinine clearance (CCr; ≥80 mL/min) and low CCr (<80 mL/min) groups and compared the findings to determine treatment safety. Results: The high and low CCr groups showed a median of 97.5 (range, 80.0–194.6) and 64.4 (range, 50.0–78.3) mL/min, respectively. The low CCr group presented more adverse reactions (ARs) of grade 3 or higher and gastrointestinal ARs of grade 2 or higher than the high CCr group (30.8% vs 15.8% and 51.9% vs 36.8%). Conclusions: The incidence of ARs associated with concurrent S-1 and RT increases in patients with low CCr; therefore, ARs should be duly considered in such patients.